Thyroglossal duct cyst, does it influence its symptoms in the oral cavity? - Caciva, Ricardo Crhistian (2017)
Fil: Caciva, Ricardo Crhistian. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Estomatología A; Argentina.